As preocupações higio-sanitárias em Portugal (2ª metade do século XIX e princípio do XX) - Cosme, João (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
With a view to resolving a significant part of the health problems of the time, food and environmental hygiene was one of the concerns of the society of the second half of the 19th century and the beginning of the 20th century. For this reason, the politicians responsible for these matters, through the publication of juridical norms, institutionalised these values and societal concerns. In this article, one analyses many of these measures promulgated in favour of food and environmental sanity.